Design of a New Chiral Deep Eutectic Solvent Based on 3-Amino-1,2-propanediol and Its Application in Organolithium Chemistry - Achille Antenucci; Matteo Bonomo; Simone Ghinato; Marco Blangetti; Stefano Dughera (Molecules, 2022)
A chiral glycerol derivative, namely 3-amino-1,2-propanediol, was employed for as the hydrogen bond donor (HBD) in the design of a new deep eutectic solvent (DES) with choline chloride acting as the hydrogen bond acceptor (HBA). The novel mixture was characterized and unambiguously classified as a DES. Furthermore, its synthetic usefulness was demonstrated in the room-temperature n-butyllithium-addition under air to carbonyl compounds and benzyl chloride. In some cases, pure products (100% conversion) were obtained by a simple extractive work-up in up to 72% isolated yield, thus suggesting the potential practical usefulness of this procedure as a green alternative to the classical Schenk procedure in volatile organic solvents for the synthesis of tertiary alcohols. The chirality of the HBD, bearing an interesting basic primary amino group, is an intriguing feature currently under investigation for further exploitation.